Controlled growth of perovskite layers with volatile alkylammonium chlorides - Park, Jaewang; Kim, Jongbeom; Yun, Hyun-Sung; Paik, Min Jae; Noh, Eunseo; Mun, Hyun Jung; Kim, Min Gyu; Shin, Tae Joo; Seok, Sang Il (Nature (London), 2023)
Controlling the crystallinity and surface morphology of perovskite layers by methods such as solvent engineering 1 , 2 and methylammonium chloride addition 3 – 7 is an effective strategy for achieving high-efficiency perovskite solar cells. In particular, it is essential to deposit α-formamidinium lead iodide (FAPbI 3 ) perovskite thin films with few defects due to their excellent crystallinity and large grain size. Here we report the controlled crystallization of perovskite thin films with the combination of alkylammonium chlorides (RACl) added to FAPbI 3 . The δ-phase to α-phase transition of FAPbI 3 and the crystallization process and surface morphology of the perovskite thin films coated with RACl under various conditions were investigated through in situ grazing-incidence wide-angle X-ray diffraction and scanning electron microscopy. RACl added to the precursor solution was believed to be easily volatilized during coating and annealing owing to dissociation into RA 0 and HCl with deprotonation of RA + induced by RA⋯H + -Cl − binding to PbI 2 in FAPbI 3 . Thus, the type and amount of RACl determined the δ-phase to α-phase transition rate, crystallinity, preferred orientation and surface morphology of the final α-FAPbI 3 . The resulting perovskite thin layers facilitated the fabrication of perovskite solar cells with a power-conversion efficiency of 26.08% (certified 25.73%) under standard illumination. In situ grazing-incidence wide-angle X-ray diffraction and scanning electron microscopy were used to evaluate the crystallization process and surface morphology of perovskite thin films coated with alkylammonium chlorides, which were used to fabricate high-efficiency perovskite solar cells.